2017
DOI: 10.1039/c7ta00589j
|View full text |Cite
|
Sign up to set email alerts
|

Improved air stability of perovskite hybrid solar cells via blending poly(dimethylsiloxane)–urea copolymers

Abstract: A hydroscopic and flexible copolymer has been successfully employed in the fabrication of perovskite solar cells with high photovoltaic performance and enhanced stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 33 publications
2
47
0
2
Order By: Relevance
“…Perovskite solar cells with improved flexibility have been reported previously . It has also been reported that polymer additives can be used to stabilize perovskite crystals against humidity‐assisted degradation . In particular, polymers that can form hydrogen bonds with perovskite components (organic cations) are considered to be effective additives.…”
Section: Resultsmentioning
confidence: 99%
“…Perovskite solar cells with improved flexibility have been reported previously . It has also been reported that polymer additives can be used to stabilize perovskite crystals against humidity‐assisted degradation . In particular, polymers that can form hydrogen bonds with perovskite components (organic cations) are considered to be effective additives.…”
Section: Resultsmentioning
confidence: 99%
“…Then the PbI 2 film was soaked in the MAI or MAI/urea solvent for several hours. MAI tends to react first at the defects and grain boundaries of PbI 2 film, and the reaction between them is very fast. In the two‐step method, the role of urea is firstly to form an adduct to slow down the formation of perovskite layers, thereby promoting the penetration of MAI solution in the PbI 2 film, and then delay the growth of grains and improve the film quality.…”
Section: Resultsmentioning
confidence: 99%
“…Polymers have potential in providing optimal morphologies and strong humidity resistance to the perovskite absorber when they are used as the ETL scaffold. However, the mesoporous polymer scaffolds often suffer as a result of their insulating character or poor conductivity limits, so they are usually used as templates but not ETLs in PSCs . In order to improve the electron transport, Tong et al reported a low‐temperature‐processed mesoporous graphene/polymer (mp‐GP)/Cs 2 CO 3 ETL for high‐performance PSCs .…”
Section: Mesoscopic Etl In Regular (N–i–p) Pscsmentioning
confidence: 99%